2016
DOI: 10.1371/journal.pone.0151501
|View full text |Cite
|
Sign up to set email alerts
|

CK19 and Glypican 3 Expression Profiling in the Prognostic Indication for Patients with HCC after Surgical Resection

Abstract: This retrospective study was designed to investigate the correlation between a novel immunosubtyping method for hepatocellular carcinoma (HCC) and biological behavior of tumor cells. A series of 346 patients, who received hepatectomy at two surgical centers from January 2007 to October 2010, were enrolled in this study. The expressions of cytokeratin 19 (CK19), glypican 3 (GPC3), and CD34 were detected by immunohistochemical staining. The clinical stage was assessed using the sixth edition tumor–node–metastasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
55
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 34 publications
4
55
3
Order By: Relevance
“…The findings of Feng et al. have indicated that the HCC tissue expression of both GPC3 and CK‐19 is correlated with local recurrence in HCC patients after surgical resection …”
Section: Prognostic Value Of Gpc3 Levelsmentioning
confidence: 99%
“…The findings of Feng et al. have indicated that the HCC tissue expression of both GPC3 and CK‐19 is correlated with local recurrence in HCC patients after surgical resection …”
Section: Prognostic Value Of Gpc3 Levelsmentioning
confidence: 99%
“…Multivariate Cox regression analysis revealed that GPC-3 is an independent risk factor for the 5-year survival (p = 0.031) and disease-free survival rates (p = 0.047). Together with tumor differentiation, the Milan criteria, and preoperative AFP, GPC-3 is a potential indicator of a poor prognosis after liver transplantation in patients with HCC and HBV-associated cirrhosis (43,44).…”
Section: Prognostic Valuementioning
confidence: 99%
“…The correlation between the HCC subtyping based on CK19 and GPC3 combined detection and tumor biology had been identified earlier15. It was observed that patients with CK19+/GPC3+ expression carried the highest risk of microvascular invasion, regional lymph node involvement, and intrahepatic and distant metastasis, followed by patients with CK19−/GPC3+, and finally the CK19−/GPC3− phenotype.…”
mentioning
confidence: 79%